2007
DOI: 10.2460/javma.231.11.1688
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for excessive tibial plateau angle in large-breed dogs with cranial cruciate ligament disease

Abstract: Results suggested that early neutering was a significant risk factor for development of excessive TPA in large-breed dogs with CCLD. Further research into the effects of early neutering on TPA and the pathophysiology of CCLD is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
2
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 18 publications
4
75
2
10
Order By: Relevance
“…One study reported a significant difference in tibial plateau angle (TPA) between dogs with and without CCL disease 62 ; however, data from multiple studies contradict this and there is no definitive evidence that either TPA or patellar tendon‐tibial plateau angle is a significant risk factor for cruciate disease in dogs. When either of these angles is considered high based on reference intervals in dogs, ex vivo research and theoretical considerations suggest there is increased CCL strain and an increased shear component of total joint force 22,24,25,27,28,30,31,33,34,43,45,47,48,52,61,63 . Thus, these components may contribute to the process of organ failure, but do not appear to be primary causal factors based on current best evidence 57,60,63–67 .…”
Section: What Are Abnormalities In Stifle Joint Biomechanics Associatmentioning
confidence: 99%
“…One study reported a significant difference in tibial plateau angle (TPA) between dogs with and without CCL disease 62 ; however, data from multiple studies contradict this and there is no definitive evidence that either TPA or patellar tendon‐tibial plateau angle is a significant risk factor for cruciate disease in dogs. When either of these angles is considered high based on reference intervals in dogs, ex vivo research and theoretical considerations suggest there is increased CCL strain and an increased shear component of total joint force 22,24,25,27,28,30,31,33,34,43,45,47,48,52,61,63 . Thus, these components may contribute to the process of organ failure, but do not appear to be primary causal factors based on current best evidence 57,60,63–67 .…”
Section: What Are Abnormalities In Stifle Joint Biomechanics Associatmentioning
confidence: 99%
“…With regard to joint disorders, one study of effects of neutering in larger breeds documents a 3-fold increase in excessive tibial plateau angle – a known risk factor for development of cranial cruciate ligament tears or rupture (CCL) [17]. Across several breeds, a study of CCL found that neutered males and females were 2 to 3 times more likely than intact dogs to have this disorder [18].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to joint disorders affected by neutering, one study documents a 3-fold increase in excessive tibial plateau angle – a known risk factor for development of CCL – in large dogs [14]. A paper on CCL found that, across all breeds, neutered males and females were 2 to 3 times more likely than intact dogs to have this disorder [15].…”
Section: Introductionmentioning
confidence: 99%